Biochemical Assessment of Insulin and Dopamine 2 Receptors in Patients with Type 2 Diabetes - Khitam Abed Sahil; Nazar Shiyaa Mohammed; Yousr Majd Jmeel; Anil K Sharma (Journal of Techniques)
Dopamine (DA) plays a key role in the body's regulation of insulin production. This study aimed to estimate insulin and dopamine 2 receptors in type 2 diabetic patients. The study included 180 subjects aged (20-65) years during the period from November 2022 to March 2023. They were divided into two groups: 120 patients with type 2 Diabetes mellitus (60 males and 60 females), and 60 healthy individuals (30 males and 30 females) as a control group. The biochemical tests (insulin and dopamine 2) were measured by the Human Insulin ELISA kit and Human Dopamine 2 receptor ELISA kit in Bioassay Technology Laboratory. The HbA1c, urea, and creatinine were measured by the kit from Roche/ Hetachi Diagnostics Ltd Company. The fasting blood glucose and HbA1c were measured to diagnose all patients with T2DM and controls to confirm the subjects with T2DM. The samples were obtained from the AL Kinday Hospital and Endocrine Center in Baghdad, Iraq.